Pengaruh Lingkungan Kerja, Keselamatan Kerja, Dan Kompensasi Terhadap Motivasi Kerja Karyawan: Studi Pada Petugas Penjaga Pintu Perlintasan Kereta Api Di Wilayah Resort 8.16 Lawang - Rian Agung Kurniawan; Budi Wahono; Muhammad Sirojuddin Amin (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract The purpose of this study is to examine how the workplace affects, occupational safety, and compensation on the work motivation of railway crossing gatekeepers in the Resort 8.16 Lawang area. The study used a survey method with a quantitative approach. The population was made up of all railway crossing gatekeepers (PJL), totaling 40 employees. Therefore, the entire population was used as a research sample using a saturated sampling technique. A questionnaire with a Likert scale was distributed to collect data. Multiple linear regression analysis was used to evaluate the data with IBM SPSS Statistics. The results of the study show that work motivation is greatly influenced by the work environment, work safety, and wages simultaneously. Additionally, each variable exhibits a positive and substantial influence on the employees’ work motivation. These findings suggest that improving the quality of the work environment, implementing effective occupational safety practices, and providing fair compensation are important factors in enhancing the work motivation of railway crossing gatekeepers. Keywords: Work Environment, Occupational Safety, Compensation, Work Motivation.